Should I stay or should I go? : a guide to knowing if your relationship can--and should--be saved - Bancroft, Lundy; Patrissi, JAC. (New York : Berkley Books, 2011)
''Is this what all couples go through?''Do I expect too much from a relationship?''Can my partner really change?''Are there steps I can take to get my relationship back on course?''When is it time to move on?' You're getting hurt over and over again, so should you stay or should you go? Every relationship has problems, but you can't figure out if yours is beyond hope. How bad is too bad--and can your man really change? Now, in this warm, supportive, and straightforward guide, Lundy Bancroft, the author of Why Does He Do That?, and women's advocate JAC Patrissi offer a way for you to practically and realistically take stock of your relationship and move forward. If you're involved in a chronically frustrating or unfulfilling relationship, the advice and exercises in this book will help you learn to - Tell the difference between a healthy--yet difficult--relationship and one that is really not working - Recognize the signs that your man has serious problems - Stop waiting to see what will happen--and make your own growth the top priority - Design a clear plan of action for you and your partner - Navigate the waters of a relationship that's improving - Prepare for life without him, even as you keep trying to make life work with him'--
Includes bibliographical references and index.
Keywords: Interpersonal relations; Couples -- Psychology; Man-woman relationships; Sex role